Impoliteness Strategies in Online Interaction: : A Case Study of Hailey Bieber’s TikTok Comment Section - Purnamasari, Mellya Dewi (Language Horizon: Journal of Language Studies, 2025)
The use of social media is now part of everyone’s life. People can leave any comments as they please, including impolite comments. These impolite comments written by people are often found in celebrity or Tik Tok influencer’s comment sections, one of them is in Hailey Bieber’s. Therefore, this study aimed to reveal impoliteness strategies using the theory of Culpeper (2005) in Hailey Bieber’s TikTok comment section and finding the reason why one type occurred more frequently than another. This study uses descriptive-qualitative methods to collect and compute the data. It is found that there are four impoliteness strategies utilized in the comment sections, those are bald-on record impoliteness, positive impoliteness, negative impoliteness, and mocking politeness or sarcasm. Moreover, sarcasm is revealed to be the most frequent type to be occurs since it contains ambiguity that can cover up the actual meaning and intention of the utterances or statements Keywords: impoliteness strategy, TikTok comments, sarcasm, Hailey Bieber.